2010
DOI: 10.1088/2040-8978/13/2/024001
|View full text |Cite
|
Sign up to set email alerts
|

The physics and applications of superconducting metamaterials

Abstract: We summarize progress in the development and application of metamaterial structures utilizing superconducting elements. After a brief review of the salient features of superconductivity, the advantages of superconducting metamaterials over their normal metal counterparts are discussed. We then present the unique electromagnetic properties of superconductors and discuss their use in both proposed and demonstrated metamaterial structures.Finally we discuss novel applications enabled by superconducting metamateri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
129
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 80 publications
(201 reference statements)
0
129
0
Order By: Relevance
“…I n recent years, the idea of using superconducting quantum interference devices (SQUIDs) and their quantum analogues (qubits) as meta-atoms in superconducting microwave metamaterials has become increasingly appealing as the attention of the community shifts towards tunability and parametric effects [1][2][3][4] . In the quantum limit, efforts to build many-qubit systems blur the border between circuit quantum electrodynamics and metamaterials [5][6][7][8] while even the classical case holds a multitude of interesting and yet unexplored possibilities.…”
mentioning
confidence: 99%
“…I n recent years, the idea of using superconducting quantum interference devices (SQUIDs) and their quantum analogues (qubits) as meta-atoms in superconducting microwave metamaterials has become increasingly appealing as the attention of the community shifts towards tunability and parametric effects [1][2][3][4] . In the quantum limit, efforts to build many-qubit systems blur the border between circuit quantum electrodynamics and metamaterials [5][6][7][8] while even the classical case holds a multitude of interesting and yet unexplored possibilities.…”
mentioning
confidence: 99%
“…The frequency and time in equation (1) are normalized to the corresponding LC SQUID frequency ω 0 = 1/ √ LC and its inverse ω where ℩ is the driving frequency, φ dc is the flux bias, and φ ac is the amplitude of the ac field. The current, i n,m , flowing in the (n, m) SQUID, normalized to the critical current of the junction, I c , is given by…”
Section: Squid Metamaterials Equationsmentioning
confidence: 99%
“…Superconducting metamaterials [1], a particular class of artificial media that rely on the extraordinary properties of superconductors at sufficiently low temperatures, have been recently attracted great attention (see e.g., reference [2]). Conventional metamaterials, that comprise highly conducting metallic elements [3,4,5], typically exhibit high losses in the frequency range where their unusual and sought properties are manifested.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the study on the negative refraction has attracted intensive interest and a large number of the negative refractive index materials have been introduced [16]. Interestingly, recent studies show that in the radio, microwave and low-terahertz frequency ranges the superconductors can behave as metamaterials and exhibit negative refraction [17]. Using the AdS/CFT correspondence, Gao and Zhang investigated the optical properties in the s-wave superconductors and found that the negative refraction does not appear in these holographic models in the probe limit [18].…”
Section: Introductionmentioning
confidence: 99%